Specific and reliable detection of Myosin 1C isoform A by RT‑qPCR in prostate cancer cells - Aleena A Saidova; Daria M Potashnikova; Anna V Tvorogova; Ivan V Maly; Wilma A Hofmann; Ivan A Vorobjev (PeerJ, PeerJ Inc., 2018)
Prostate cancer (PC) diagnostics and treatment often present a challenging task due to cancer subtype heterogeneity and differential disease progression in patient subgroups. Hence, the critical issue is finding a reliable and sensitive diagnostic and prognostic PC marker, especially for cases of biopsies with low percentages of cancer cells. Isoform A of myosin 1C was shown to be expressed in PC cells and responsible for their invasive properties, however, its feasibility for diagnostic purposes remains to be elucidated. To verify the role of myosin 1C isoform A mRNA expression as a putative prostate cancer marker we performed RT‑qPCR normalized by three reference genes (GAPDH, YWHAZ, HPRT1) on PC3, RWPE‑1, LNCaP and 22Rv1 cell lines. Myosin 1C isoform A detection specificity was confirmed by immunofluorescence staining, cancer and non‑cancer prostate cell lines were immunophenotyped by flow cytometry. We report a distinct difference in myosin 1C isoform A mRNA levels in malignant (PC3) and benign (RWPE‑1) prostate cell lines and suggest a combination of three reference genes for accurate data normalization. For the first time we provide an immunophenotype comparison of RWPE‑1 and PC3 cells and demonstrate that RT qPCR analysis of MYO 1C A using appropriate reference genes is sufficient for PC detection even in low‑abundance cancer specimens.
Keywords: Myosin 1C A isoform; Prostate cancer; RT‑qPCR; diagnostic marker